Oral comfort: A new concept to understand elderly people's expectations in terms of food sensory characteristics. (December 2018) - Vandenberghe-Descamps, Mathilde; Labouré, Hélène; Septier, Chantal; Feron, Gilles; Sulmont-Rossé, Claire
Highlights: A definition of oral comfort when eating a food in the elderlies is proposed. Understanding oral comfort allowed the development of a questionnaire. Assessing oral comfort in cereal and meat products enabled a product discrimination. This concept should be taken into account when designing food for elderly. Abstract: In the elderly population, ageing frequently impacts on the different aspects of oral physiology that play a key role in eating behavior. In the context of an aging population, it is crucial to develop a food supply tailored for the elderly people in order to prevent the onset of malnutrition. To meet this challenge, we looked for the concept of "oral comfort" when eating a food. The present study aimed at i) exploring the concept of oral comfort when eating according to elderly people in order to develop a questionnaire to evaluate the oral comfort when eating a food and ii) asking elderly people to evaluate various meat and cereal products using this questionnaire. Results of focus groups highlighted that oral comfort when eating a food is a multi-dimensional concept which includes dimensions related to food oral processing (ability to form and swallow food bolus), food sensory properties (texture and taste) and to a lesser extent pain sensations. Furthermore, the oral comfort questionnaire developed in the present study enabled a discrimination of products and highlighted the fact that some products supposed to fit with elderly people capacities and needs were not rated as the most comfortable foods by the elderly people. The concept of oral comfort when eating a food should be taken into account by those who are willing to design food products tailored to the elderly population. The questionnaire could be an interesting tool to assess oral comfort when eating a food in the elderly population.